2007
DOI: 10.1534/genetics.107.075424
|View full text |Cite
|
Sign up to set email alerts
|

A Linkage Map Reveals a Complex Basis for Segregation Distortion in an Interpopulation Cross in the Moss Ceratodon purpureus

Abstract: We report the construction of a linkage map for the moss Ceratodon purpureus (n ¼ 13), based on a cross between geographically distant populations, and provide the first experimental confirmation of maternal chloroplast inheritance in bryophytes. From a mapping population of 288 recombinant haploid gametophytes, genotyped at 121 polymorphic AFLP loci, three gene-based nuclear loci, one chloroplast marker, and sex, we resolved 15 linkage groups resulting in a map length of $730 cM. We estimate that the map cove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
133
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(140 citation statements)
references
References 67 publications
6
133
1
Order By: Relevance
“…It should therefore be ideal for mapping PAR genes and testing these ideas. PAR genes of such species, including several plants (Liu et al 2004;McDaniel et al 2007;Spigler et al 2008), could thus be used to search for evidence of SA polymorphisms. However, detailed genetic maps are available in few dioecious plants.…”
mentioning
confidence: 99%
“…It should therefore be ideal for mapping PAR genes and testing these ideas. PAR genes of such species, including several plants (Liu et al 2004;McDaniel et al 2007;Spigler et al 2008), could thus be used to search for evidence of SA polymorphisms. However, detailed genetic maps are available in few dioecious plants.…”
mentioning
confidence: 99%
“…Cronberg and Natcheva 2002). If hybridisation explains the 'incorrect' placements of D. turgescens PT1088 and D. lycopodioides PT190 in the plastid network, then the maternal parent must have been D. lycopodioides in the first case, and D. turgescens in the second since, as far as we know, chloroplasts are maternally inherited in bryophytes (Duckett et al 1983;McDaniel et al 2007;Natcheva and Cronberg 2007a). Besides hybridisation and introgression, horizontal chloroplast transfer has been shown to occur (Cristina Acosta and Premoli 2010;Stegemann et al 2012), although this has not yet been shown to occur in bryophytes.…”
Section: Discussionmentioning
confidence: 99%
“…Fusarium subglutinans alleles could have had fewer negative interactions with the hybrid genetic background, than those of F. circinatum (Burke and Arnold 2001;Myburg et al 2004). This genic incompatibility is characterized by the proper functioning of alleles in their separate genetic backgrounds, but these alleles can become incompatible when brought together in a hybrid (McDaniel et al 2007). The observed bias could also be due to increased viability of ascospores containing F. subglutinans alleles.…”
Section: Discussionmentioning
confidence: 99%